2015
DOI: 10.1111/jbi.12670
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene expansion of ponderosa pine (Pinus ponderosa) in the Central Rocky Mountains, USA

Abstract: Aim Ponderosa pine (Pinus ponderosa) experienced one of the most extensive and rapid post-glacial plant migrations in western North America. We used plant macrofossils from woodrat (Neotoma) middens to reconstruct its spread in the Central Rocky Mountains, identify other vegetation changes coinciding with P. ponderosa expansion at the same sites, and relate P. ponderosa migrational history to both its modern phylogeography and to a parallel expansion by Utah juniper (Juniperus osteosperma).Location Central Roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
(102 reference statements)
1
11
0
Order By: Relevance
“…Our estimates of growth also do not consider potential threshold responses of mortality. For example, paleo‐reconstructions have found that ponderosa pine distribution has decreased with decreasing July precipitation (Norris, Betancourt, & Jackson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our estimates of growth also do not consider potential threshold responses of mortality. For example, paleo‐reconstructions have found that ponderosa pine distribution has decreased with decreasing July precipitation (Norris, Betancourt, & Jackson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Pleistocene populations of Haplotype 3 were likely separated from haplotype 6 by the Rocky Mountains during glacial periods, and refugial locations may have occurred in Arizona and New Mexico [ 9 ], where our models now predicted the highest probability of occurrence for the haplotype, in summer monsoon-dominated climates. Norris et al [ 7 ] reconstructed the northward expansion of P . p .…”
Section: Discussionmentioning
confidence: 99%
“…This broad distribution reflects not only the influence of contemporary climate and environmental settings, but also the influence of past climate variability that forced range expansion and contraction and limited some populations to spatially isolated refugia [ 4 ]. Climate-induced range shifts combined with topographic isolation likely contributed to intraspecific genetic diversification over time [ 5 ], and spatial patterns among both historical and contemporary ponderosa pine populations suggest that genetic divisions occupy well-defined climate niches [ 4 7 ]. A clear understanding of the relationships between genetically distinct populations and climate may be key to management and conservation of ponderosa pine under future climate change [ 6 , 8 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pines were able to colonize large areas after the glacial era (Macdonald, Cwynar, & Whitlock, ). Pinus ponderosa experienced a long delay establishment, followed by rapid expansion across large parts of the central Rocky Mountains in North America, suggesting climate‐ rather than dispersal‐driven expansion (Norris, Betancourt, & Jackson, ). Desponts and Payette () reconstructed the postglacial history of P. banksiana and found that this species formed small stands from 300 to 2,400 B.P.…”
Section: Why Have Pines Become the Dominant Conifer Taxon In Many Envmentioning
confidence: 99%